Imaging of cardiovascular complications in patients with systemic lupus erythematosus. (October 2015) - Lin, K; Lloyd-Jones, D M; Li, D; Liu, Y; Yang, J; Markl, M; Carr, J C
In the long-term survival of patients with systemic lupus erythematosus (SLE), cardiovascular disease (CVD) is a leading cause of death. Recently, multimodality cardiovascular imaging methods have been adopted for the evaluation of cardiovascular risk, which has shown to be associated with both traditional cardiovascular risk factors and SLE-specific conditions. Quantitative imaging biomarkers, which can describe both morphological and functional abnormalities in the heart, are expected to provide new insights to stratify cardiovascular risks and to guide SLE management by assessing individual responses to therapies either protecting the cardiovascular system or suppressing the autoimmune reactions. In this review, we will discuss cutting-edge cardiovascular imaging techniques and potential clinical applications and limitations of those techniques for the evaluation of major SLE-related heart disorders.